Basis properties in the spaces L and C of the systems of exponential functions with degeneration - Veliev, S. G. (Журнал математичної фізики, аналізу, геометрії, 2005)
Systems of exponential functions with degenerating coefficients are considered. Necessary and sufficient conditions of the completeness and minimality of these systems are obtained in the spaces of summable and continuous functions under definite conditions on the coefficients. Mathematical Subject Classification: 47E05.